Identifying Language in the Context of Financial Crimes on Social Media in the Policies and Programs of the Elected Government of the Republic of Indonesia for 2024 (A Forensic Linguistics Study) - Indira Tiardana Kusuma; Suhartono Suhartono; Abdul Kholiq (International Journal Labs, 2026)
The rapid growth of social media has transformed digital communication patterns and created new challenges related to language misuse, including expressions that potentially constitute financial and reputational crimes in the public sphere. The misuse of language in social media discussions regarding government policies and programs may influence public perceptions, spread misleading information, and trigger conflicts among communities. This study aims to identify and analyze forms of language crimes found on social media within the context of financial and policy-related discussions of the elected Government of the Republic of Indonesia in 2024 through a forensic linguistics perspective. This research employed a qualitative descriptive method using forensic semantic and forensic pragmatic approaches. Data were collected through observation, documentation, reading, and note-taking techniques from social media posts and comments on platforms such as YouTube, Instagram, and X (Twitter). Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that language crimes occurring on social media include slander, insults, and defamation expressed through negative labeling, accusations, and degrading statements. Forensic semantic analysis reveals the use of lexical and connotative meanings aimed at damaging the image and credibility of individuals or groups, while forensic pragmatic analysis identifies expressive speech acts intended to influence public opinion. The study concludes that social media language abuse requires careful contextual interpretation and legal awareness because not all negative expressions represent crimes without considering communicative intent, factual basis, and social impact.